Nototanoides oliveri, a new sponge-dwelling nototanaid tanaidacean (Crustacea, Tanaidomorpha, Tanaidacea) from eastern Gulf of Mexico, with an illustrated taxonomic key, and the first record of harpacticoid copepods within the marsupium of ovigerous female tanaids - Morales-Núñez, Andrés G.; Ramos-Tafur, Gabriel E. (Zootaxa, 2023)
A new species of tanaidacean, Nototanoides oliveri sp. nov. from the eastern part of the Gulf of Mexico is described and illustrated. The new species appears to be most closely related to the recently described western Atlantic species, N. polytrichus. It can be easily distinguished from that species, as well as the other members of the genus, N. trifurcatus and N. ohtsukai, by a combination of characters, including: (1) female antennular article-3 with up to 11 aesthetascs (2) female maxilliped palp article-2 with multifurcate spiniform seta and (3) male cheliped basis having mid-ventral margin swollen, forming a rounded apophysis/protuberance. In addition, an unknown living harpacticoid copepod is reported for the first time within the marsupium of ovigerous females of Tanaidacea. An illustrated key to the four species comprising the genus Nototanoides is presented.